Asymmetric Policy on Border Management - Elias Mite; Ramos Da Chrismas; Yohanes Endes Teturan; Vinsenco R Serano; Nur Jalal; Alexander P Tjilen (Musamus Journal of Public Administration, 2020)
The management of state borders between Indonesia and PNG holds potential problems in the form of differences in socio-economic conditions between the two countries. While socially and culturally, people in the two countries have close kinship ties. This paper intends to recommend an asymmetric policy for managing national border areas, especially between Merauke and PNG. The conclusion of this study is that the adoption of the ChinaVietnam border management model can be applied in the management of the Indonesia-PNG border. This adoption is accompanied by several strategies in the form of: acceleration of construction of facilities and infrastructure, strengthening the socio-economic conditions of border communities, human resource development and strengthening of good institutional aspects.